Effect of jogging and core training after supramaximal exercise on recovery - Burak Cılhoroz; Menderes Kabadayı; Murat Elıoz; Pelin Akyol; Tulin Akman (Selcuk University, 2014)
The aim of this study is to compare the effect of jogging and core training after supramaximal exercise on recovery.  30 male basketball players (age; 23,57±1,32 years) playing in the regional basketball league participated the study.  Subjects were required to visit the laboratory on 2 occasions, each separated by 3 days for recovery by 2 different methods. Subjects performed jogging or core training after Wingate Supramaximal Exercise (WSE) for recovery.  The order of the 2 different recovery methods (jogging and core training) was selected randomly to prevent an order effect. Resting Heart Rate (HR) and blood lactic acid (LA) values of subjects were measured and then they performed WSE. Following the test, LA measurements were repeated in the 1st min, 5th min and 10th min of recovery. HR was measured right after the test and at the every 1 minute of 10 minutes recovery.  LA values were not found significantly different between two recovery methods (p gt;0.05). It was determined that all HR values except   resting, right after, 4th, 7th and 9th min of recovery with core training was significantly lower than the same minutes of recovery with jogging (p lt;0.05 and p lt;0.01).  It was determined that the effect of jogging and core training on recovery LA level, carried out after supramaximal exercise were not different but they were different on recovery HR. It was determined that core training lowered HR faster.